2014
DOI: 10.1111/apa.12764
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis shows that infants who have suffered neonatal sepsis face an increased risk of mortality and severe complications

Abstract: Infants who have suffered neonatal sepsis face an increased risk of mortality and severe complications such as brain damage and, or, neurodevelopmental delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 29 publications
1
86
0
Order By: Relevance
“…Despite recent advances in neonatal intensive care, sepsis remains an important cause of morbidity and mortality, particularly among preterm infants [1,2] . Neonatal sepsis causes poor neurodevelopmental outcomes in preterm infants [3][4][5][6][7] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in neonatal intensive care, sepsis remains an important cause of morbidity and mortality, particularly among preterm infants [1,2] . Neonatal sepsis causes poor neurodevelopmental outcomes in preterm infants [3][4][5][6][7] .…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal sepsis is a major cause of morbidity and mortality in neonatal intensive care units [1] and is prevalent in premature infants [2] . Many clinical studies have…”
Section: Introductionmentioning
confidence: 99%
“…Infants who have had culture-proven late-onset neonatal bloodstream infections have higher mortality than those who have not had these infections [1,6]. Late-onset neonatal bloodstream infections in very low birth weight infants bestow independent risks to long-term child development, in addition to the wellrecognized risks bestowed by brain injury, bronchopulmonary dysplasia, and retinopathy of prematurity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Infants who have suffered neonatal sepsis face an increased risk for brain damage and neurodevelopmental delays [2,3], whereas, experimental data have shown that inflammation/infection early in life may alter the developmental trajectory of the immune system and the brain [4,5]. Early diagnosis and management of neonatal infection improves prognosis; thus, the identification of new or complementary biomarkers of neonatal infection or sepsis is of potential importance [6].…”
Section: Introductionmentioning
confidence: 99%